LIFE AND LANGUAGE: Sign of Authenticity in What People Speak - Vineeth, Francis (Journal of Dharma, 2010)
The Word, imperishable is the firstborn of Truth, Mother of the Veda and hub of immortality. May she come to us in happiness in the sacrifice! May she, our protecting Goddess, be easy of entreaty.